Influência de diferentes pontos de estimulação elétrica de carcaças sobre a qualidade da carne de novilhas Nelore - Guimarães, Leonardo Virgílio Gregório (2017)
In order to verify the influence of electrical stimulation at different points on the carcass, 60 Nelore heifers aged up to 24 months from the same farm of origin were evaluated. The chemical characteristics (pH, temperature) and physical (color, softness, loss by cooking) of the meat were evaluated. The animals were randomly divided into 4 experimental groups: without electrical stimulation (NS), electrical stimulation in the lateral region (COS), electrical stimulation in the calcaneus (CAL) and double electric stimulation in the calcaneal and lateral regions. For the analysis of performance and physical and chemical characteristics, three statistical models were used, one for each type of characteristic. There was no difference in the temperature and pH drop between the experimental groups until the 12 hours of cooling, and after 18 hours all the experimental groups were accredited to the recommended value (pH <5.8). The temperature drop did not differ between stimulated and non-stimulated carcasses. For softness and loss by cooking, there was no interference of the stimulation, but, it was observed that the cooling time and technological maturation significantly interfered in the softness. For coloring, the effect of the stimulation in the "a" and "b" shades and in the technological maturation times for all shades was observed, and for the shades L and b, the effect of the cooling was also observed. The electrical stimulation, in general, did not improve the physical characteristics of the meat (better softness, less loss by cooking); which demonstrates the need for more studies to prove the site of stimulation that most aggregates the final quality of the meat.